A meta-analysis of the group-size effect on vigilance in mammals. (22nd June 2021) - Beauchamp, Guy; Li, Zhongqiu; Yu, Cong; Bednekoff, Peter A; Blumstein, Daniel T
Abstract: Group-size effects, whereby antipredator vigilance decreases as group size increases, are widely reported in mammals and birds but a meta-analysis has only been conducted in birds. We systematically reviewed the literature on mammalian group-size effects, estimated the effect sizes in each study, and conducted a phylogenetic meta-analysis. We obtained 296 effect sizes from 97 species belonging to 10 Orders and 26 Families. Overall, effect sizes indicated a moderate negative effect of group size ( r = −0.44), but 43% of the effect sizes were compatible with a null effect of group size. There was significant heterogeneity in effect sizes. Weaker effect sizes occurred when vigilance was measured as a frequency or a duration rather than as a percentage of time spent vigilant, when measured in closed habitats, during the reproductive season, and in mixed-sex groups or during times when juveniles were absent. We infer a "file drawer problem" because there were relatively few studies with smaller sample sizes reporting small group-size effects. The results confirm the importance of group size in explaining variation in mammalian vigilance but also suggest which a substantial amount of variation remains unexplained. We suggest that future studies should aim to study mammalian group-size effects by quantifying the percentage of time allocated to vigilance rather than lower-power methods such as frequency or duration of vigilance. Abstract : In animals, large groups are expected to be safer, allowing group members to invest less in vigilance against predators at no increased risk to themselves. Using previously published research, we examined how much vigilance decreases with group size in mammals. Pooling across many studies, we found a moderate negative effect of group size as predicted. Several variables, including how vigilance is estimated, social conditions, and habitat structure can influence the strength of this association.